2019
DOI: 10.1155/2019/6215739
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modelling of a Stepped Spillway with Various Step Layouts

Abstract: A traditional stepped spillway is prone to cavitation risks. To improve its hydraulic behaviors, distorted step faces and pool weirs are devised. By numerical modelling, comparative studies are conducted to look into the flow features. The pressures on step surfaces of the unconventional layouts exhibit 3D distributions. Pool weirs are essential in increasing both the min. and max. pressure loads. Pressures on the downstream bed show a unique pattern for V- and inverted V-shaped models, with the extreme pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Li et al [13] devised distorted step faces and pool weirs to improve the hydraulic behaviors for traditional stepped spillways. By numerical modelling, comparative studies were conducted to look into the flow features.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [13] devised distorted step faces and pool weirs to improve the hydraulic behaviors for traditional stepped spillways. By numerical modelling, comparative studies were conducted to look into the flow features.…”
Section: Introductionmentioning
confidence: 99%
“…Hekmatzadeh et al (2018) demonstrated more efficiency of the flat stepped spillway in comparison to the pooled stepped spillway if the spillway slope exceeds 14°. Li et al (2019) provided numerical insight into the hydraulic characteristics of V-shaped spillways with several step layouts. Arjenaki & Sanayei (2020) carried out a numerical analysis to investigate the effects of different types of step geometries on the energy dissipation rate of stepped spillways.…”
Section: Introductionmentioning
confidence: 99%
“…e stepped spillway drainage structure dates back to 2500 years ago [10], and it has good energy dissipation; it can greatly shorten the length of the stilling pool and reduce the project's investment costs. With the development of roller concrete damming technology, this technique has been widely applied [11], and scholars both at home and abroad have conducted in-depth studies on it [12,13]. Wu et al [14] found that the location of the inception point of the air entrainment for the stepped spillway is much nearer to the top of the spillway than a smooth spillway, which led to the high energy dissipation ratio of the stepped spillway.…”
Section: Introductionmentioning
confidence: 99%